(untitled) (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2026)
Environmental degradation has driven businesses globally to adopt green marketing for sustainability. While validated internationally, the specific impact of these strategies on Nepalese consumers remains distinct. This study examines the influence of green marketing tools— specifically Environmental Beliefs, Eco-labeling, Eco-branding, Environmental Advertising, and Green Packaging—on consumer buying behavior in Kathmandu. Using a descriptive and explanatory research design, a valid sample of 310 Kathmandu residents was surveyed via convenience sampling. Primary data was collected using a 5-point Likert scale questionnaire. Data analysis utilizing SPSS employed Cronbach’s Alpha for reliability, alongside Pearson correlation and multiple regression to test the hypotheses. Results indicate that green marketing tools significantly explain consumer buying behavior (R² = 0.462, p < 0.001). Eco-branding (β = 0.268) and Green Packaging (β = 0.197) were the strongest predictors, followed by Eco-labeling and Environmental Beliefs. Conversely, Environmental Advertising showed an insignificant negative impact (β = −0.024, p = 0.710), indicating it does not independently drive purchase decisions. The study concludes that while consumers in Kathmandu are environmentally conscious and responsive to tangible green indicators like trusted brands and packaging, they exhibit skepticism toward promotional advertising. Thus, the effectiveness of green marketing relies more on product credibility than on promotional claims.